2010
DOI: 10.1590/s0066-782x2010001500011
|View full text |Cite
|
Sign up to set email alerts
|

Prevalência e preditores antropométricos de pressão arterial elevada em escolares de João Pessoa - PB

Abstract: Background: Arterial hypertension (AH) belongs to the group of cardiovascular diseases with the highest mortality in the world and its onset can occur in childhood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…Although a small number of studies [19, 21, 25, 26, 30, 33] have addressed the cardiovascular and metabolic comorbidities in this population, the results showed significant prevalence of hypertension and hypercholesterolemia in young Brazilians. For being children and adolescents, borderline and/or high values for systolic blood pressure (SBP) and diastolic blood pressure (DBP) predispose greater risk of developing cardiovascular problems later in adulthood [21].…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Although a small number of studies [19, 21, 25, 26, 30, 33] have addressed the cardiovascular and metabolic comorbidities in this population, the results showed significant prevalence of hypertension and hypercholesterolemia in young Brazilians. For being children and adolescents, borderline and/or high values for systolic blood pressure (SBP) and diastolic blood pressure (DBP) predispose greater risk of developing cardiovascular problems later in adulthood [21].…”
Section: Resultsmentioning
confidence: 96%
“…From the 17 articles selected, seven of them [19, 21, 22, 25, 26, 30, 33] also presented the information on the prevalence of hypertension and dyslipidemia associated with overweight and obesity in Brazilian children and adolescents at the municipal level. In relation to hypertension, studies have been conducted in the south region ( n = 2), southeast ( n = 2), and northeast ( n = 1) with prevalence that may reach values of up to 13.6% in the northeast [26], 13.5% in the south [16], and 11.7% in the southeast [20].…”
Section: Resultsmentioning
confidence: 99%
“…A prevalência de obesidade central foi de 4,9% (IC95%=4,3;5,5), sendo mais elevada nos meninos (5,9%;IC95%=4,9;6,8)…”
Section: Resultsunclassified
“…In João Pessoa (PB), Queiroz et al 6 assessed 750 schoolchildren aged 6 to 9 years and found a prevalence of central obesity of 2.4%. In Fortaleza (CE), Damasceno et al 7 assessed children aged 6 to 11 years and found a prevalence of 30.9%.…”
Section: Introductionmentioning
confidence: 99%
“…They conclude that a high frequency of uncontrolled hypertensive patients and cardiovascular risks in HIV-infected patients point out to the need for preventive and therapeutic measures against hypertension in this group. Queiroz et al39 evaluate the prevalence of high blood pressure in schoolchildren from public schools and its association with anthropometric indicators. They identified an association between excess weight with high blood pressure levels, which emphasizes the need for intervention and for nutritional status control measures, such as dietary education programs aimed at the prevention and treatment of obesity as a risk factor for cardiovascular diseases in the pediatric and older age ranges.…”
Section: Introductionmentioning
confidence: 99%